Accumulation of 90SR by Betula pendula within the East Ural Radioactive Trace zone. (September 2022) - Mikhailovskaya, Ludmila N.; Pozolotina, Vera N.; Modorov, Makar V.; Kukarskih, Vladimir V.; Guseva, Valentina P.; Mikhailovskaya, Zinaida B.; Shimalina, Nadezhda S.
Abstract: This study was conducted in 2010–2020 at the head of the East Ural Radioactive Trace (EURT), which was formed in 1957 as a result of the Kyshtym accident at the Mayak Production Association. The main contaminant in this zone is the long-lived radionuclide Strontium-90 (90Sr). Secondary forests dominated by silver birch (Betula pendula) occupy 45% of the EURT area. Concentration of 90Sr in birch leaves and small branches was higher than that in the trunks. The 90Sr content in birch sapwood varied slightly in the radial direction and did not depend on tree age. This was due to the dynamic equilibrium of the migration processes responsible for the accumulation and horizontal transfer of 90Sr. The 90Sr concentration increases in false heartwood, which is formed as a result of the secondary metabolism of dying parenchyma in the inner part of sapwood and is characterised by a high content of ash elements. The concentration of radionuclides in the aboveground organs of birch increased and the aggregated transfer factors (Tag) decreased with an increase in the soil contamination density, in accordance with the power function. The reasons for these patterns are also discussed. Highlights: Tag decrease with a rise of soil contamination density according to power function. 90 Sr content in birch's organs increases following the soil contamination density. 90 Sr concentration in birch leaves and small branches is higher than that in trunks. The 90 Sr content in birch sapwood varies slightly in the radial direction. 90 Sr concentrations increase in false heartwood due to high ash content.